Clinical spectrum transition and prediction model of nonalcoholic fatty liver disease in children with obesity - Zhou, Xuelian; Lin, Xiufu; Chen, Jingnan; Pu, Jiaqi; Wu, Wei; Wu, Zhaoyuan; Lin, Hu; Huang, Ke; Zhang, Li; Dai, Yangli; Ni, Yan; Dong, Guanping; et al. (Frontiers in Endocrinology, 2022)
Objective: This study aims to elaborate the clinical characteristics, establish and validate a prediction model for pediatric NAFLD. Materials and methods: The retrospective study enrolled 3216 children with obesity from January 2003 to May 2021, they were divided into obese without NAFLD, nonalcoholic fatty liver (NAFL) and nonalcoholic steatohepatitis (NASH) group. Clinical data were retrieved, gender and chronologic characteristics were compared between groups. Data from the training set (3036) were assessed using univariate analyses and stepwise multivariate logistic regression, by which a nomogram was developed to estimate the probability of NAFLD. Another 180 cases received additional liver hydrogen proton magnetic resonance spectroscopy (1H-MRS) were as validation set. Results: The prevalence of NAFLD was higher in males than in females and increased over recent 19 years. Totally 1915 cases were NAFLD, the peak onset age was 10-12 years old. Hyperuricemia ranked first in childhood NAFLD comorbidities, followed by dyslipidemia, hypertension, metabolic syndrome (MetS), dysglycemia. The AUROC of the eight-parameter nomogram including waist-to-height ratio (WHtR), hip circumference (HC), triglyceride glucose-waist circumference (TyG-WC), alanine aminotransferase (ALT), high density lipoprotein cholesterol (HDL-C), apolipoprotein A1(ApoA1), insulin sensitivity index [ISI (composite)] and gender for predicating NAFLD was 0.913 (sensitivity 80.70%, specificity 90.10%). Calibration curves demonstrated a great calibration ability of the model. Conclusion and Relevance: NAFLD is the most common complication in children with obesity. The nomogram based on anthropometric and laboratory indicators performed well in predicting NAFLD, which can be used as a quick screening tool to assess pediatric NAFLD in children with obesity.